A role for angiogenesis in rheumatoid arthritis - Stupack,D.G. (1999)
Rheumatoid arthritis (RA) is a chronic debilitating disease characterized by distinct autoimmune, inflammatory and fibrovascular components which lead to synovial proliferation and joint destruction. However, existing treatments specifically target only autoimmune and inflammatory components despite the fact that neovascularization of the inflamed synovium is a hallmark of rheumatoid arthritis. Angiogenesis may contribute to synovial growth, leukocyte recruitment and tissue remodeling, thus potentiating disease progression. Although no therapies currently target angiogenesis, several existing therapies have anti-angiogenic activity. Recent advances in anti-angiogenic strategies in oncology, including the identification of integrin avß3 as a crucial effector of angiogenesis, suggest a means to assess the role of angiogenesis in rheumatoid arthritis. Synovial endothelial cells have been shown to express integrin avß3, suggesting that these cells may be targeted for angiogenesis inhibition. Prior studies in rat arthritis models have shown benefit after the addition of broad spectrum integrin antagonists. However, formal assessment of integrin-targeted anti-angiogenic activity is now underway. These controlled studies will be important in assessing the efficacy of therapies which target angiogenesis in RA.